2001
DOI: 10.1002/jmv.2020.abs
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for rotavirus in Argentina

Abstract: Group A rotaviruses are the major cause of severe gastroenteritis in young children worldwide. Because rotavirus vaccination appeared imminent, a nationwide surveillance program was organized between October 1996 and October 1998 in the largest Argentine cities. Surveillance for disease burden, rotavirus detection, and rotavirus typing was undertaken at nine locations. Results showed rotavirus to be associated with 42% of diarrhea admissions. Although the prevalent G types changed from year to year, common G t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
69
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(89 citation statements)
references
References 0 publications
15
69
1
4
Order By: Relevance
“…Many studies have shown that rotavirus is an important cause of diarrhoea in children in developed and developing countries [13]. Most cases occur in children less than 5 years of age.…”
Section: Rotavirus Genotypingmentioning
confidence: 99%
“…Many studies have shown that rotavirus is an important cause of diarrhoea in children in developed and developing countries [13]. Most cases occur in children less than 5 years of age.…”
Section: Rotavirus Genotypingmentioning
confidence: 99%
“…Surveys around the globe indicates that G1P [8], G2P [4], G3P [8] and G4P [8] are the most common G and P types combinations (24,38,40). However, recently, genotypes G5, G8, G9, G11 and G12, and/or new combinations of G and P were identified in Latin America and in other parts of the world (10,38,41).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20 (38.5%) samples were characterized as G genotype mixtures and P mixtures were found in 16 (29.6%) samples. P [4] was found in 55.6% of samples, P[8] in 51.9% and P[6-M37 like] in 22.3% of cases. P[6-Gottfried like] and P[11] were detected only in mixtures.…”
mentioning
confidence: 99%
“…Some of these may only have local significance (e.g. G5 in parts of Brazil and G8 in Malawi; Bok et al, 2001b;Cunliffe et al, 2001b), but at least one serotype, G9, was demonstrated to have dispersed worldwide (Ramachandran et al, 1996;Unicomb et al, 1999;Griffin et al, 2000;Iturriza-Gó mara et al, 2000;Palombo et al, 2000;Araú jo et al, 2001;Bok et al, 2001a;Cunliffe et al, 2001a;Bányai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%